Fixed trandolapril and verapamil SR combination effectiveness in arterial hypertension patients - L. G. Ratova; I. E. Chazova; M. B. Antsiferov; Yu. B. Belousov; V. S. Moiseev; M. V. Shestakova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effectiveness, rates of target blood pressure (BP) level achievement, and safety of a fixed-dose trandolapril and verapamil SR combination (Tarka) in patients with Stage I-II arterial hypertension (AH).Material and methods. The study initially included 100 AH patients; 7 dropped out, and 4 were excluded due to inclu- sion criteria violation. The study protocol was completed  by 89 participants (36% men, 64% women), aged 27-74 years (mean age 56,6±10,8 years), with mean AH duration of 9,1±8 years. After 3-14-day wash-out period, clinical mean systolic BP (SBP clin.) level was 158,1±9,3/95,1±8,0 mm Hg, and heart rate (HR) level – 75,2±7,4 bpm. BP level corresponded to Stage I AH in 40,5% of the patients, and to Stage II AH – in 59,5%. Eighty five per cent of the participants received antihypertensive medications, 17% had Type 2 diabetes mellitus (DM-2), 20% were smokers.Results. In all patients, Tarka therapy (2/180 mg/d) was associated with adequate BP reduction. Antihypertensive effect reached its maximum at Week 4 of the treatment. Twelve-week therapy resulted in significant decrease in BP clin., (∆=-28,9±11,0/-18,4±8,1;  p<0,001) and HR (∆=-6,0±6,6;  p<0,0001). Target SBP, DBP or SBP+DBP levels were achieved in 82%, 96%, and 80%, respectively. In DM-2 patients, target BP level was achieved in 71%. According to 24-hour BP monitoring data, after 12 weeks of treatment, BP was normalized in 68 participants: in 88% – for SBP, in 99% – for DBP, and in 88% – for both SBP and DBP. In all patients, the treatment was well tolerated;  adverse effects (AE) were registered in 9 individuals only.Conclusion. Good antihypertensive  effectiveness of fixed trandolapril and verapamil combination facilitated target BP level achievement in 80% of the patients, with low AE rates. Therefore, the medication could be recommended at initial treatment stage.